Identification of [18F]TRACK, a fluorine-18-labeled tropomyosin receptor kinase (Trk) inhibitor for PET imaging - Bernard-Gauthier, Vadim; Mahringer, Anne; Wängler, Björn; Wängler, Carmen; Fricker, Gert (Journal of medicinal chemistry, 2018)
Changes in expression and dysfunctional signaling of TrkA/B/C receptors and oncogenic Trk fusion proteins are found in neurological diseases and cancers. Here, we describe the development of a first 18F-labeled optimized lead suitable for in vivo imaging of Trk, [18F]TRACK, which is radiosynthesized with ease from a nonactivated aryl precursor concurrently combining largely reduced P-gp liability and improved brain kinetics compared to previous leads while displaying high on-target affinity and human kinome selectivity.
Gesehen am 24.07.2019
Published: December 19, 2017
Im Titel ist die 18 in [18F]TRACK hochgestellt